Letter from Federico Schnell to Max Bredig, December 31, 1944 - Schnell, Federico (1944)
Federico Schnell writes to his friend Max Bredig (1902-1977) shortly before the New Year. Fritz muses about his image of Max's life, and updates Max on his own home, wife, and child. Fritz also writes with news that he received a letter from his brother, Alfred (1900-1944).
Keywords: Bredig, Max Albert, 1902-1977; Schnell, Federico; Schnell, Eva, 1913-1944; Schnell, Alfred, 1900-1944